TNFRSF11B modulates Marek’s disease virus infection by regulating apoptosis in chicken embryo fibroblasts - Zheng, Gang; Yang, Yuqin; Du, Yushuang; Liu, Yongzhen; Lian, Ling (Frontiers in Veterinary Science, 2026)
IntroductionMarek’s disease, caused by the oncogenic Marek’s disease virus (MDV), remains a major threat to poultry production. Host immune responses and apoptosis pathways play critical roles in MDV pathogenesis, yet the underlying mechanisms are not fully understood.MethodsChicken embryo fibroblasts (CEF) were treated with poly I:C to assess its effect on MDV infection, followed by transcriptome profiling to identify differentially expressed genes. Functional assays using siRNA knockdown and overexpression of TNFRSF11B were performed to evaluate its impact on viral infection and apoptosis.ResultsPoly I:C treatment significantly reduced MDV infection in CEF. Transcriptome analysis identified 274 DEGs, among which TNFRSF11B was notably downregulated. Consistently, MDV infection suppressed TNFRSF11B expression in both CEF and spleen tissues. Functional assays revealed that knockdown of TNFRSF11B enhanced MDV infection, whereas its overexpression suppressed MDV infection. Furthermore, MDV infection induced substantial cell apoptosis, and TNFRSF11B knockdown further exacerbated this effect, as demonstrated by elevated CASP3 expression and higher apoptosis rates. A strong positive correlation was observed between MDV infection levels and apoptosis rates (R2 = 0.9895, p < 0.0001).DiscussionOur findings indicated TNFRSF11B could modulate MDV infection through collaborating with MDV to modulate cell apoptosis. This study provides new insights into the pathogenesis of MDV and potential antiviral strategies targeting MDV/TNFRSF11b—cell apoptosis.